The Influence of Merariq Culture on Early Wedding in East Lombok District, NTB - Fibrianti; Sasteri Yuliati (Institute of Computer Science (IOCS), 2020)
Culture Merariq (mating kidnapped) a unique phenomenon in bu public resources capsicum were to marry a woman in Sasak chilli should be kidnapped in advance without seeking approval from her parents. Culture Merariq unconsciously contributes to the high number of early marriage in Lombok. In general, the purpose of this study was to explore information about the influence of Merariq Culture (kidnap Marriage) with the incidence of early marriage in East Lombok Regency. The research method used is qualitative research by conducting in-depth interviews with several informants. The subject of this research is the informants who married early under the age of 20 years for women and 21 years for men in the region of eastern Lombok is as much as seven informants, as well as related parties such as Indigenous Leaders, Religious Leaders, Community Leaders and UPTD-PPA. The sampling technique was purposive; thus, the information to be extracted in this study was the influence of Merariq culture with the incidence of early marriage in East Lombok district. Based on the results of the above research, after conducting interviews with informants, it was found that 5 out of 7 informants married by merariq . It can be concluded that the Culture of merariq contributed high rates of early marriage in eastern Lombok, customary culture merariq is not one kar e na to do this practice there are procedures ways and the rules do not set a culture necessarily do that